Long‐term outcomes of laparoscopic versus open liver resection for intrahepatic combined hepatocellular‐cholangiocarcinoma with propensity score matching. Issue 4 (9th February 2022) - Lee, Seung Jae; Kang, So Hyun; Choi, YoungRok; Lee, Boram; Hong, Suk Kyun; Cho, Jai Young; Yi, Nam‐Joon; Lee, Kwang‐Woong; Suh, Kyung‐Suk; Han, Ho‐Seong
Abstract: Background: Combined hepatocellular‐cholangiocarcinoma (cHCC‐CCA) is a rare primary hepatic neoplasm. Currently, there are no well‐structured studies that analyze the feasibility of laparoscopic liver resection in cHCC‐CCA alone. This retrospective cohort study aimed to compare the long‐term survival of laparoscopic liver resection with open liver resection in cHCC‐CCA. Methods: Patients with a postoperative pathologic report of cHCC‐CCA who underwent liver resection from August 2004 to December 2017 were included in this study. Kaplan–Meier survival analysis was performed to analyze the 3‐y disease‐free survival and 3‐y overall survival. Propensity score matching was done to reduce the influence of confounding variables. Results: A total of 145 patients were pathologically confirmed to have cHCC‐CCA, of which 10 patients were excluded due to having received palliative surgery. Of the remaining 135 patients, 43 underwent laparoscopic and 92 underwent open liver resection; propensity score matching yielded 30 patients for each group. The 3‐y overall survival was 38 (88.4%) in the laparoscopic group and 84 (91.3%) in the open group before propensity score matching ( P = .678), and 25 (83.3%) and 28 (93.3%), respectively, after matching ( P = .257). The 3‐y disease‐free survival was 24 (55.8%) in the laparoscopic group and 32 (34.8%) in the open group before matching ( P = .040), and 17 (56.7%) and 16 (53.3%), respectively, after matching ( P = .958). The hospital stay was shorter in the laparoscopic group before and after matching, while other operative outcomes were similar in both groups. Conclusion: Laparoscopic liver resection for cHCC‐CCA is technically feasible and safe, having a shorter hospital stay without compromising oncological outcomes. Abstract : In this article we compared the long‐term outcomes of laparoscopic versus open liver resection for combined hepatocellular‐cholangiocarcinoma and found out that laparoscopic surgery is safe and feasible for this disease. The importance of this finding is that it provides justification for performing laparoscopic liver resection for patients with combined hepatocellular‐cholangiocarcinoma.